Industrial nation : work, culture and society in Scotland, 1800-present - Knox, William, 1948- (Edinburgh University Press, 1999)
Industrial Nation is the first systematic social and economic history of modern Scotland. It is illustrated with contemporary illustrations with guides to further reading.